Thermal proteome profiling identifies the membrane-bound purinergic receptor P2X4 as a target of the autophagy inhibitor indophagolin. Issue 12 (16th December 2021) - Carnero Corrales, Marjorie A.; Zinken, Sarah; Konstantinidis, Georgios; Rafehi, Muhammad; Abdelrahman, Aliaa; Wu, Yao-Wen; Janning, Petra; Müller, Christa E.; Laraia, Luca; Waldmann, Herbert
Summary: Signaling pathways are frequently activated through signal-receiving membrane proteins, and the discovery of small molecules targeting these receptors may yield insights into their biology. However, due to their intrinsic properties, membrane protein targets often cannot be identified by means of established approaches, in particular affinity-based proteomics, calling for the exploration of new methods. Here, we report the identification of indophagolin as representative member of an indoline-based class of autophagy inhibitors through a target-agnostic phenotypic assay. Thermal proteome profiling and subsequent biochemical validation identified the purinergic receptor P2X4 as a target of indophagolin, and subsequent investigations suggest that indophagolin targets further purinergic receptors. These results demonstrate that thermal proteome profiling may enable the de novo identification of membrane-bound receptors as cellular targets of bioactive small molecules. Graphical abstract: Highlights: An indoline-containing autophagy inhibitor was identified through a phenotypic screen Target identification using thermal proteome profiling suggested P2X4 as a target P2X4 was confirmed as a target through CETSA, ITDRF, and calcium influx assays Computational target ID and further profiling confirmed activity at several receptors Abstract : Carnero Corrales et al. employed thermal proteome profiling (TPP) to enable the identification of membrane-bound receptors as cellular targets of a small-molecule autophagy inhibitor. This work showcases TPP as an important technique for target identification of membrane proteins and provides a link between purinergic receptors and autophagy.